Protective Effect of Rhizophora mucronata Leaves on Hepatic Oxidative Stress, Serum Cytokines and Insulin Resistance in Type 2 Diabetic Rats - Ray, Moumita; Indu, Rania; Bhattacharya, Sangita; Adhikari, Anjan (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: Glucose homeostasis is mainly controlled by liver, which is altered in diabetes. Metabolic alteration and insulin resistance develop due to oxidative stress and inflammation. Plant secondary metabolites have therapeutic relevance in diabetes and associated complications. Present study evaluated the effect of hydro-alcoholic extract of Rhizophora mucronata leaves (RME) in diabetes induced hepatic oxidative stress, serum cytokines and insulin resistance in Streptozotocin-Nicotinamide induced type 2 diabetic rats. Materials and Methods: The diabetic rats were treated with extract for 28 days and liver markers as well tissue antioxidant parameters (nitric oxide, reduced glutathione, superoxide dismutase), lipid peroxide contents and histology of liver were studied. Serum insulin, C-peptide were estimated and insulin resistance parameters were evaluated using homeostasis model assessment (HOMA). Serum cytokines like tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β) were analyzed. Results: Rhizophora mucronata leaves extract decreased the elevated hepatic enzymes, restored the hepatocellular damages by reducing the lipid peroxides and free radicals near normal, as well as inducing the cellular antioxidants. Correlation analysis of insulin resistance with the cytokines revealed significant positive association with TNF-α (r=0.662, p<0.01). RME in both 200mg/kg and 400mg/kg doses reduced the serum pro-inflammatory cytokines and also inhibited HOMA-IR potentially by 72% than the untreated diabetic control rats. Conclusion: Present study indicated the hepatoprotective effect of Rhizophora mucronata leaves against diabetes induced damage, could maintain normal glucose homeostasis. Anti-diabetic action of this mangrove plant might be mediated through significant antioxidant action with reduction of inflammatory cytokines as well as amelioration of insulin resistance.
Keywords: Antioxidant; Cytokines; Hepatoprotective; Insulin resistance; Rhizophora; mucronata